THE ROLE OF BIOCHEMICAL BIOMARKERS FOR NEURONAL ACTIVITY AND CLINICAL NEUROPSYCHOLOGICAL TESTS IN PATIENTS WITH CAROTID STENTING. (June 2022) - Yaneva-Sirakova, Teodora; Vassilev, Dobrin; Karamfiloff, Kiril; Hristova, Julieta; Shumkova, Monika; Dimov, Anastas; Traykov, Latchezar
Abstract : Objective: The application of carotid stenting is rising. We need biomarkers, which would guide us and help in the assessment of its effectiveness regarding brain blood flow and cognition. Potential candidate biomarkers are the markers for neuronal activity Brain Derived Neurotrophic Factor (BDNF) and Neural Growth Factor (NGF). Their serum concentration is correlated with brain hemodynamics and function. Design and method: We included 78 patients: 39 with hemodynamically significant carotid stenoses and 39 controls - without. All underwent ultrasound diagnostics and ELISA test of BDNF and NGF serum concentrations. The biomarkers for neural activity in patients with significant carotid stenoses, were tested at 3 phases: before (n34), 24 h. post (n22) and at least 1 month after stenting (n18). Cognitive functions were assessed with MMSE and MoCA. On their basis the patients were classified as having or not potential mild cognitive impairment (MCI) Statistical analysis was done with SPSS 19(IBM), p < 0.05, CI 95%. Results: There was a significant difference in the BDNF concentration before and after carotid stenting (p < 0.0001); in BDNF [p = 0.001, CI (-5.11- -1.44)] and NGF [p = 0.049, CI (0.64–347.75)] between patients with significant stenoses/stenting and controls. Periprocedural hypotension, stroke history and MCI did not influence biomarkers concentrations. Correlation analysis showed intermediate positive correlation between systolic, diastolic, pulse pressure and biomarkers at a certain time of sampling. This association was proven for the systolic blood pressure by the regression analysis too. The mean values of BDNF after stenting raised and for NGF lowered after carotid stenting. Conclusions: A larger sample is needed to prove further our results, namely: 1. Arterial blood pressure is an important factor for BDNF and NGF concentrations; 2. The correlation between these markers and interventional treatment may be not linear; 3. There are significant differences in the serum concentrations of biomarkers for neural activity between patients with and without significant carotid stenoses. Research Grant 2020 from Medical University Sofia, Bulgaria, contract 133/24.06.2020